Pathogenic mechanisms in systemic lupus erythematosus - PERL, ANDRAS (2010)
Systemic lupus erythematosus (SLE) is a chronic inflammatory disease characterized by the dysfunction of T cells, B cells, and dendritic cells and by the production of antinuclear autoantibodies. This editorial provides a synopsis of newly discovered genetic factors and signaling pathways in lupus pathogenesis that are documented in 11 state-of-the-art reviews and original articles. Mitochondrial hyperpolarization underlies mitochondrial dysfunction, depletion of ATP, oxidative stress, abnormal activation, and death signal processing in lupus T cells. The mammalian target of rapamycin, which is a sensor of the mitochondrial transmembrane potential, has been successfully targeted for treatment of SLE with rapamycin or sirolimus in both patients and animal models. Inhibition of oxidative stress, nitric oxide production, expression of endogenous retroviral and repetitive elements such as HRES-1, the long interspersed nuclear elements 1, Trex1, interferon alpha (IFN-α), toll-like receptors 7 and 9 (TLR-7/9), high-mobility group B1 protein, extracellular signal-regulated kinase, DNA methyl transferase 1, histone deacetylase, spleen tyrosine kinase, proteasome function, lysosome function, endosome recycling, actin cytoskeleton formation, the nuclear factor kappa B pathway, and activation of cytotoxic T cells showed efficacy in animal models of lupus. Although B cell depletion and blockade of anti-DNA antibodies and T–B cell interaction have shown success in animal models, human studies are currently ongoing to establish the value of several target molecules for treatment of patients with lupus. Ongoing oxidative stress and inflammation lead to accelerated atherosclerosis that emerged as a significant cause of mortality in SLE.